Genetic diversity and evolution of Pneumocystis fungi infecting wild Southeast Asian murid rodents. Issue 7 (9th November 2017) - Latinne, Alice; Bezé, François; Delhaes, Laurence; Pottier, Muriel; Gantois, Nausicaa; Nguyen, Julien; Blasdell, Kim; Dei-Cas, Eduardo; Morand, Serge; Chabé, Magali
Abstract: Pneumocystis organisms are airborne-transmitted fungal parasites that infect the lungs of numerous mammalian species with strong host specificity. In this study, we investigated the genetic diversity and host specificity of Pneumocystis organisms infecting Southeast Asian murid rodents through PCR amplification of two mitochondrial genes and tested the co-phylogeny hypothesis among these fungi and their rodent hosts. Pneumocystis DNA was detected in 215 of 445 wild rodents belonging to 18 Southeast Asian murid species. Three of the Pneumocystis lineages retrieved in our phylogenetic trees correspond to known Pneumocystis species, but some of the remaining lineages may correspond to new undescribed species. Most of these Pneumocystis species infect several rodent species or genera and some sequence types are shared among several host species and genera. These results indicated a weaker host specificity of Pneumocystis species infecting rodents than previously thought. Our co-phylogenetic analyses revealed a complex evolutionary history among Pneumocystis and their rodent hosts. Even if a significant global signal of co-speciation has been detected, co-speciation alone is not sufficient to explain the observed co-phylogenetic pattern and several host switches are inferred. These findings conflict with the traditional view of a prolonged process of co-evolution and co-speciation of Pneumocystis and their hosts.